Model for Developing a Multicultural Islamic Religious Education Curriculum in Islamic Higher Education - Rodliyatun, Mushbihah; Nugroho, Puspo; Baidhawy, Zakiyuddin (Program Studi Pendidikan Agama Islam, 2022)
This study aims to determine the importance of implementing multicultural education and strategies in developing multicultural-based Islamic religious education (PAI) curriculum in the Undergraduate Islamic Religious Education Study Program of the Faculty of Tarbiyah and Teacher Sciences (FTIK), IAIN Salatiga. This qualitative research used observation, interview, and documentation methods. The results uncovered that multicultural education is crucial for students. The lecturer's strategy in implementing the learning process was adjusted to the curriculum. Also, there is a curriculum evaluation by opening up students' thinking insights and developing student potential through expanding Islamic knowledge insights on contemporary issues. The strategies used in instilling multicultural education include (1) fostering noble morals and developing inter-religious harmony; (2) multicultural education was carried out comprehensively; (3) lecturers implemented multicultural values both in lectures and off-campus activities; (4) building teamwork involving stakeholders; (5) the curriculum development model was conducted through subject matter curriculum; (6) institutional support for multicultural-based Islamic religious education curriculum development. Implementing multicultural education in the Undergraduate Islamic Religious Education Study Program of the Faculty of Tarbiyah and Teacher Sciences (FTIK), IAIN Salatiga, can be a real solution to heterogeneous or plural conflicts as a preventive effort in undergoing socio-cultural problems.